2021
DOI: 10.31742/ijgpb.81.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pigeonpea genotypes with wider adaptability to rainfed environments through AMMI and GGE biplot analyses

Abstract: Pigeonpea [Cajanus cajan (L.) Millspaugh] is an important pulse crop grown under Indian rainfed agriculture. Twenty eight pigeonpea genotypes were tested for stability and adaptability across ten rainfed locations in the States of Telangana and Karnataka, India using AMMI (additive main effects and multiplicative interaction) model and GGE (genotype and genotype by environment) biplot method. The grain yields were significantly affected by environment (56.8%) followed by genotype × environment interaction (27.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Gauch (2013) suggested that the most accurate model for AMMI can be predicted by using the first two IPCAs. Several researchers used the first two IPCAs for the GGE biplot analysis because they explained a greater percentage of the G × E interaction for sorghum (Al-Naggar et al, 2018), barley (Vaezi et al, 2017), pigeonpea (Rao et al, 2020;Kumar et al, 2021), wheat (Verma et al, 2015), and maize (Solomon et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gauch (2013) suggested that the most accurate model for AMMI can be predicted by using the first two IPCAs. Several researchers used the first two IPCAs for the GGE biplot analysis because they explained a greater percentage of the G × E interaction for sorghum (Al-Naggar et al, 2018), barley (Vaezi et al, 2017), pigeonpea (Rao et al, 2020;Kumar et al, 2021), wheat (Verma et al, 2015), and maize (Solomon et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The vector view of GGE biplot in the genotype-focused scaling measured their dissimilarity in discriminating the genotypes (Kumar et al, 2021). For grain yield, sorghum varieties PYPS1, PYPS 6, PYPS 7, PYPS 9, PYPS 10, PYPS 17, PYPS 18, and PYPS 19 showed the same group position.…”
Section: Gge Biplot Of Genotype View For Grain Yieldmentioning
confidence: 99%
“…To encounter this requirement, various crop improvement programs have been initiated all over the world (Anonymous, 2019). In any crop improvement program, the performance of promising genotypes has been tested over different locations each year to identify the genotypes having both high yield qualities and wider adaptability over different environmental conditions (Kumar et al, 2021, Reddy et al, 2022. In Multilocation trials (MLT), most frequently, it is noticed that the genotypes respond differently to the diverse environmental conditions; this differential response of genotypes over diverse environments is known as Genotype environment interaction (GEI) (Pham et al, 1988, Farias et al, 2016, Pagi et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…An important characteristic of this GGE biplot is that it removes the environment main effect and retains and combines genotype main effect and GEI. Thus, the biplot generated from the MLT data contains only G and GEI (Kang, 2002, Kumar et al, 2021, Sharma et al, 2016. GGE biplot and AMMI analyses has been carried out in understanding GEI in many crop species including pigeon pea (Rao et al, 2022, Reddy et al, 2022, Kumar et al, 2021, Sharma et al, 2016; wheat (Verma et al, 2021, Singh et al, 2019, Jeberson et al, 2017; ground nut (Khan et al, 2021); maize (Bozovic et al, 2020, Oliveira et al, 2010; rice (Chandra Mohan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Reddy et al (2011) evaluated ten pigeonpea genotypes over three years under rainfed conditions using the Eberhart and Russell method to select those with good stability for grain yield, number of pods, and seed size. In another study, Kumar et al (2021) recommended two out of 28 genotypes evaluated under rainfed conditions in ten locations using AMMI and GGE biplot analyses.…”
Section: Introductionmentioning
confidence: 99%